2010
DOI: 10.1007/s00464-009-0860-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic appendectomy for acute appendicitis: a preliminary experience

Abstract: The SILA technique is safe and feasible for selected patients with noncomplicated acute appendicitis. Compared with other transumbilical techniques of appendectomy, SILA has the advantages of feasibility without endoscopic skills and an acceptable operative time. Technical refinements and accomplished learning probably will enable its wider use for more patients with acute appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…Twenty studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] including 584 patients met the definition criteria for 'SPILA unassisted' approaches. The use of special multi-conduit ports was reported in four studies [4][5][6][7] ( Fig 1).…”
Section: Spila Unassistedmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] including 584 patients met the definition criteria for 'SPILA unassisted' approaches. The use of special multi-conduit ports was reported in four studies [4][5][6][7] ( Fig 1).…”
Section: Spila Unassistedmentioning
confidence: 99%
“…Techniques placing multiple ports through closely spaced fascial incisions with a single abdominal skin incision were reported in ten studies. [8][9][10][11][12][13][14][15][16][17] Generally, papers described the introduction of three trocars through the fascia, two providing channels for instruments and one providing access for a 5-10mm laparoscopic camera with an angulated lens. In studies where three ports were not placed, a third instrument, often a grasper, was placed directly though a fascial stab incision.…”
Section: Spila Unassistedmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[12][13][14][15][16][17][18] But the successive rate of SILS technique can be confirmed by prospective clinical trial but no study was found yet.…”
Section: Discussionmentioning
confidence: 98%
“…20 They found lower pain scores and better cosmesis in the SILS group and felt that it was a suitable alternative to standard laparoscopic appendicectomy in uncomplicated cases of appendicitis despite the additional time required.…”
Section: Appendicectomymentioning
confidence: 93%